Outreach obstetrics training in Western Australia improves neonatal outcome and decreases caesarean sections - Maouris, P.; Jennings, B.; Ford, J.; Karczub, A.; Kohan, R.; Butt, Janice; Evans, S.; Gee, V. (Informa Healthcare, 2010)
The objective of this study was to determine the effect of a multi-professional outreach obstetric training programme on perinatal and neonatal outcomes. This was a retrospective comparison of 5-min low Apgar scores, stillbirth, perinatal death and moderate/severe hypoxic ischaemic encephalopathy rates in 127,753 infants born in Western Australia before and after the introduction of training in rural and remote areas. Following the introduction of the training programme, there was a highly significant (p0.003) decrease in the rate of infants born with low 5-min Apgar scores (from 20.4 to 15.4/1,000 live births). While the changes in the other three outcomes were not significant, all three demonstrated a trend for improvement in the intervention area. This is the second study of an educational intervention in obstetrics to demonstrate improvement in neonatal outcome and the first to be associated with a decrease in caesarean sections.